The Geoglobus acetivorans Genome: Fe(III) Reduction, Acetate Utilization, Autotrophic Growth, and Degradation of Aromatic Compounds in a Hyperthermophilic Archaeon - Mardanov, Andrey V. (Appl Environ Microbiol, 2015)
Geoglobus acetivorans is a hyperthermophilic anaerobic euryarchaeon of the order Archaeoglobales isolated from deep-sea hydrothermal vents. A unique physiological feature of the members of the genus Geoglobus is their obligate dependence on Fe(III) reduction, which plays an important role in the geochemistry of hydrothermal systems. The features of this organism and its complete 1,860,815-bp genome sequence are described in this report. Genome analysis revealed pathways enabling oxidation of molecular hydrogen, proteinaceous substrates, fatty acids, aromatic compounds, n-alkanes, and organic acids, including acetate, through anaerobic respiration linked to Fe(III) reduction. Consistent with the inability of G. acetivorans to grow on carbohydrates, the modified Embden-Meyerhof pathway encoded by the genome is incomplete. Autotrophic CO(2) fixation is enabled by the Wood-Ljungdahl pathway. Reduction of insoluble poorly crystalline Fe(III) oxide depends on the transfer of electrons from the quinone pool to multiheme c-type cytochromes exposed on the cell surface. Direct contact of the cells and Fe(III) oxide particles could be facilitated by pilus-like appendages. Genome analysis indicated the presence of metabolic pathways for anaerobic degradation of aromatic compounds and n-alkanes, although an ability of G. acetivorans to grow on these substrates was not observed in laboratory experiments. Overall, our results suggest that Geoglobus species could play an important role in microbial communities of deep-sea hydrothermal vents as lithoautotrophic producers. An additional role as decomposers would close the biogeochemical cycle of carbon through complete mineralization of various organic compounds via Fe(III) respiration.